Analysing admission control for AODV and DSR routing protocol in mobile ad-hoc network - Folayo Aina; Sufian Yousef; Opeyemi Osanaiye (Bulletin of Electrical Engineering and Informatics, 2021)
The widespread deployment of mobile ad-hoc network (MANET) in the areas of agriculture, military defence, weather forecasting and disaster control has necessitated the implementation of admission control within a network for a guaranteed quality of service (QoS). Admission control organises traffic flows to ensure the network medium is fairly shared among various nodes in the network. Various admission control algorithms have been proposed in the literature, using different metrics and parameters to achieve different admission control quality. In this work, we propose an Admission control in mobile ad-hoc network routing (ACMANR) using both bandwidth capacity and resource estimation to achieve a good QoS. Furthermore, we analyse the behaviour of two well-known routing protocols in wireless network, ad hoc on-demand distance vector (AODV) and dynamic source routing (DSR), in our proposed admission control algorithm. Simulation results obtained from our proposed admission control algorithm using OPNET show that AODV routing protocol had a better throughput while DSR produced a better delay with lower overhead in MANET. Our proposed approach also shows better performance in terms of throughput and delay when compared with the state-of-the-art admission control routing using AODV and DSR.